The relationship between loan sales and bank risk: conventional and Islamic bank perspective / Nor Salmiza Salim - Salim, Nor Salmiza (2007)
This study examine the risk behavior of the loan sales activity in Malaysia. This is because bank rebalance their loan portfolio exposure by selling loans in the secondary mortgage market. This study comprise the sample of the Conventional bank and Islamic bank which is local own bank and foreign own bank in Malaysia which provide housing from 2000 until 2006 for yearly basis. The method used in this research is multiple analysis. This study finds that there is a relationship between loan sales and bank risk in conventional bank. Meanwhile there is no relationship between loan sales and bank risk Islamic bank. For the Conventional bank, ASSETS (natural logarithm of total assets) is most significant independent variable that gives an effect towards the bank risk Meanwhile for Islamic bank, LNSLD (loan sold to total asset ratio) is the most significant effect towards the bank risk.